EVIDENCE OF THE BACTERIAL NATURE OF THE WENDOMAN ORGANISMS NEMIANA SIMPLEX - Reshetnyk, M.; Gritsenko, V.; Martyshyn, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nemiana simplex were found in Vendian deposits of Transnistria a hundred years ago. They are present in layers with determined age of 557 million. There are fourteen places with such fossils in the world. Nemiana simplex are the markers of all deposits of the Yampilian layers of the Vendian. We need to take a closer look at the Nemiana simplex analysis, as their exact nature has not been determined so far. They were considered to be raindrops, jellyfish or polyps, which is not justified. The large fluctuations in their size, and the peculiarities of their location relative to each other, indicate their biological nature. Usually, these fossils have the appearance of convex lenticular projections on the lower surfaces of sandstone layers 1-40 mm in size. They do not have any signs of the mouth opening and any other structural elements of the intestinal cavity. There are similar Nemiana prints of Beltanella and Beltanelliformis. Beltanelliformis has recently been recognized as "benthic colonies of cyanobacteria" by organic petrified films, sometimes preserved on their prints. Nemiana's prints do not contain such petrified films on the surface of the nuclei, so one cannot ascertain from biochemical analysis what they were during lifetime. Nemiana is not similar to Beltanelliformis: the distinctive features of Beltanelliformis are the absence of pronounced convex casts and concentric folds along the contour of flat prints. Although there are differences in the shape of the prints, Beltanelliformis and Nemiana are the most similar among the Vendian fossils. Given that Beltanelliformis are reflections of cyanodacetrians, we can assume that Nemiana is also a cyanobacterium. The print sizes of Nemiana simplex Palij are close to the size of modern spherical colonies of cyanobacteria Nostoc prunum. Large colonies of modern Nostoc prunum are often surrounded by smaller colonies, and in Nemiana simplex prints large prints together with smaller ones create a "cluster". Such clusters consist of entire "settlements". Nostoc colonies can appear very close to the main colony, creating "kidneys", with Nemiana simplex prints showing such "buds". Colonies of Nostoc cyanobacteria are widespread in fresh water, less often in the seas; Nemiana is found in deposits of huge deltas, that is, also in significantly desalinated seawater. It is likely that such Nostoc forms existed earlier than 550 million years ago and are still preserved in the Nemiana simplex prints on the Yampilian sandstones. Nemiana simplex prints are found on all modern continents, which indicates the conjugacy of the sea basins and the homogeneous climatic conditions on the planet during the Upper Vendee. The restoration of "settlements" of Nemiana simplex, which were systematically covered with sandy sediments, indicates their high ability to survive and the variability of reproduction.
Keywords: Precambrian; Vendian; Ediacaran biota; Vendian Transnistria; Nemiana simplex; colonies of cyanobacteria; reproduction of cyanobacteria; photosynthesis of cyanobacteria